Heterogeneous catalytic oxidation for lignin valorization into valuable chemicals: what results? What limitations? What trends?. Issue 7 (28th January 2016) - Behling, R.; Valange, S.; Chatel, G.
Abstract : This is a critical review on lignin valorization through oxidation reactions focusing on innovative approaches involving heterogeneous catalysis and unconventional activation methods and solvents. Abstract : Lignin, a renewable polymer derived from the lignocellulosic biomass represents more than 20% of the total mass of the Earth's biosphere. However, 98% of lignin is burned as a source of energy in the pulp and paper industry, essentially due to its complex structure. Today, the valorization of lignin into the production of value-added chemicals represents a real challenge in terms of both sustainability and environmental protection. The present contribution aims to provide a critical discussion on the crucial choice of the starting material to study lignin valorization. Next, a comparison between the different oxidation routes investigated by chemists over the past several years is presented, with emphasis on the major difficulties encountered. The main current challenges regarding the heterogeneous catalytic oxidation of lignin and its derivatives are also highlighted. Particular focus is given to innovative strategies favoring mild reaction conditions. Finally, we provide some recommendations and routes worthy of interest in this studied area of research in order to generate value-added chemicals from lignin oxidation through the use of heterogeneous catalysts.